2019
DOI: 10.3390/su11133623
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Feng, X., et al. Gas Multiple Flow Mechanisms and Apparent Permeability Evaluation in Shale Reservoirs. Sustainability 2019, 11, 2114

Abstract: The authors did not notice during the proofreading phase that we have accidentally deleted a related reference of Figure 1 [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 1 publication
0
34
0
1
Order By: Relevance
“…The core-level spectrum of Fe 2p is given in Figure 2c; the signals centered at 710.1 and 723.7 eV are attributed to Fe 2p 1/2 and Fe 2p 3/2 , which are caused by Fe 3þ in the sample. [42] The peak at 714.8 eV is the satellite peak. The O 1s spectrum ( Figure 2d) was deconvoluted into three different peaks situated at 529.7, 531.2, and 533.1 eV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The core-level spectrum of Fe 2p is given in Figure 2c; the signals centered at 710.1 and 723.7 eV are attributed to Fe 2p 1/2 and Fe 2p 3/2 , which are caused by Fe 3þ in the sample. [42] The peak at 714.8 eV is the satellite peak. The O 1s spectrum ( Figure 2d) was deconvoluted into three different peaks situated at 529.7, 531.2, and 533.1 eV.…”
Section: Resultsmentioning
confidence: 99%
“…[40,41] Among so many kinds of binary-transition metal oxides, zinc ferrite (ZnFe 2 O 4 ) has been specifically studied as a lithium-ion battery anode given its low price, nontoxicity, environmental friendliness, and high theoretical lithium storage capacity. [42] Nonetheless, the research on ZnFe 2 O 4 anodes for SIBs is scarcely reported, and the electrochemical reaction for reversible sodium storage of the material is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…3a-c, and the materials were too frail to be tensile tested. This is partially attributed to low viscosities (<400 mPa) [33]. Samples spun from 14, 16, and the 18% w/v for the DMF:EtOAc were easily released from the collecting plate and were fully characterized and discussed below.…”
Section: Morphological Characterizationmentioning
confidence: 99%
“…PCPU is a thermoplastic PU (TPU), which is a class of polymers that possess excellent properties, including toughness, abrasion resistive, excellent hydrolytic stability, elastomeric, and durability, making it versatile for widespread uses [26][27][28][29][30][31][32][33][34][35][36]. Because of its biocompatibility, non-toxicity, robustness, and functionality, TPUs can be used in the biomedical industry as implantable devices (vascular grafts, pacemaker leads, blood bags, bladders, and artificial heart valves) and medical applications [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…[112] PC-PU nanofibers were fabricated via electrospinning using DMF and THF as the mixed solvent. [113] Moreover, a series of biodegradable electrospun poly(ether carbonate urethane) urea materials were synthesized, and the elasticity exhibited the native annulus fibrous tissue. [114] The electrospun PTMC/ gelatin (Gt) composite fiber scaffolds were reinforced by modified nHA with oleic acid (OA).…”
Section: Electrospinning Nanofibersmentioning
confidence: 99%